Analisis Kualitas Larutan Mol (Mikroorganisme Lokal) Berbasis Ampas Tahu - NI WAYAN MARSININGSIH; A A NGURAH GEDE SUWASTIKA; NI WAYAN SRI SUTARI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Analysis of Local Mikroorganisms Solution Quality Based on Tofu dregs. The experiment was conducted at the Soil Laboratory, Faculty of Agriculture, Udayana University in January until March 2014. The purpose of this research was to determine the effects of concentration and length of fermentation tofu dregs to the quality of local microorganisms solution. The design of this research used a randomized block design factorial pattern. The first factor was the concentration of tofu dregs consisted of 0 g; 300 g; and 600 g. The second factor was the length of fermentation, consisted of one, three, and five weeks. The observed parameters are: the nature of biological, physical and chemical solution of local microorganisms. Physical characteristics include color and odor, biological properties covering a total population of bacteria and fungi. Chemical properties include pH, total-N content, and available-P. The result of this research showed that treatment of 600 g tofu dregs and five weeks length of fermentation provides the best results. It can be seen from the total population bacteria (29,80 x 108 cfu mL-1), total-N (0,06 %) and available-P (199,38 mg kg-1). Keywords: tofu dregs, concentration, length of fermentation, local microorganisms